Penerapan metode pencatatan dan penilaian atas persediaan bahan baku pada Dolphin Donuts Bakery Manado - Pogaga, Angelica Claudia; Pangemanan, Sifrid S; Warongan, Jessy D. L (Universitas Sam Ratulangi, 2019)
Inventories are assets that are held for sale in the normal course of business or goods that are used or consumed in production to be sold. For companies, inventory is a very important asset because with the company’s inventory can maintain it’s survival. The problem that often occurs in inventory accounting is recording and valuation. The purpose of this research is determine the suitability of the application of recording and valuation or raw material inventories at Dolphin Donuts Bakery Manado with the Statement of Financial Accounting Standards for Entities without Public Accountability (SAK ETAP). Dolphin Donuts Bakery Manado is a company engaged in the food industry that produces a variety of breads, pastries, donuts and birthday cakes. The method used in this research is descriptive qualitative method. Based on research results obtained that method of recording inventories is not all in accordance with SAK ETAP. Whereas the valuation of raw material inventories applied by Dolphin Donuts Bakery Manado is in accordance with the Statement of Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) Chapter 11 Regarding Inventories.